A Single Nucleotide Polymorphism in SH2B3/LNK Promotes Hypertension Development and Renal Damage. Issue 9 (28th September 2022) - Alexander, Matthew R.; Hank, Samuel; Dale, Bethany L.; Himmel, Lauren; Zhong, Xue; Smart, Charles D.; Fehrenbach, Daniel J.; Chen, Yuhan; Prabakaran, Nitin; Tirado, Brian; Centrella, Megan; Ao, Mingfang; et al.
Abstract : Background: SH2B3 (SH2B adaptor protein 3) is an adaptor protein that negatively regulates cytokine signaling and cell proliferation. A common missense single nucleotide polymorphism in SH2B3 (rs3184504) results in substitution of tryptophan (Trp) for arginine (Arg) at amino acid 262 and is a top association signal for hypertension in human genome-wide association studies. Whether this variant is causal for hypertension, and if so, the mechanism by which it impacts pathogenesis is unknown. Methods: We used CRISPR-Cas9 technology to create mice homozygous for the major (Arg/Arg) and minor (Trp/Trp) alleles of this SH2B3 polymorphism. Mice underwent angiotensin II (Ang II) infusion to evaluate differences in blood pressure (BP) elevation and end-organ damage including albuminuria and renal fibrosis. Cytokine production and Stat4 phosphorylation was also assessed in Arg/Arg and Trp/Trp T cells. Results: Trp/Trp mice exhibit 10 mmHg higher systolic BP during chronic Ang II infusion compared to Arg/Arg controls. Renal injury and perivascular fibrosis are exacerbated in Trp/Trp mice compared to Arg/Arg controls following Ang II infusion. Renal and ex vivo stimulated splenic CD8 + T cells from Ang II-infused Trp/Trp mice produce significantly more interferon gamma (IFNg) compared to Arg/Arg controls. Interleukin-12 (IL-12)-induced IFNg production is greater in Trp/Trp compared to Arg/Arg CD8 + T cells. In addition, IL-12 enhances Stat4 phosphorylation to a greater degree in Trp/Trp compared to Arg/Arg CD8 + T cells, suggesting that Trp-encoding SH2B3 exhibits less negative regulation of IL-12 signaling to promote IFNg production. Finally, we demonstrated that a multi-SNP model genetically predicting increased SH2B3 expression in lymphocytes is inversely associated with hypertension and hypertensive chronic kidney disease in humans.. Conclusions: Taken together, these results suggest that the Trp encoding allele of rs3184504 is causal for BP elevation and renal dysfunction, in part through loss of SH2B3-mediated repression of T cell IL-12 signaling leading to enhanced IFNg production.